Liquidity, Capital Structure, Investment Decisions and Investment Opportunity Set (IOS) on Company Value: Likuiditas, Struktur Modal, Keputusan Investasi dan Investment Opportunity Set (IOS) Terhadap Nilai Perusahaan - Damayanti, Hariani Oktavia; Nurasik, Nurasik (Universitas Muhammadiyah Sidoarjo, 2023)
Many previous sources have described various factors that affect firm value so that there are inconsistencies between one study and another. For this reason, this study aims to determine the effect of liquidity, capital structure, investment decisions and Investment Opportunity Set (IOS) on firm value. The research method used is a qualitative research method. The data used is a type of secondary data. The population in this study are all property and real estate sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period as many as 60 companies. Samples were taken using purposive sampling technique. Data were analyzed using multiple linear regression analysis technique with the help of SPSS 25 application. The result of this research is that liquidity and capital structure variables have no effect on firm value. On the other hand, the investment decision variables and the Investment Opportunity Set (IOS) are considered to have a partial effect on firm value.